Association of contributing factors of over-weight and obesity among urban school going adolescent girls of Cooch Behar district, West Bengal, India - Bhowmik, Sutapa; Khatun, Argina (International Journal Of Community Medicine And Public Health, 2025)
Background: Developing countries are experiencing changes in child and adolescent nutrition because of the nutritional changes, demographic and epidemiological conversion and these situation makes impact on changes in lifestyle patterns, food consumption pattern and economic changes. The objective of the study to survey current status of prevalence of overweight-obesity among urban Bengalee Hindu adolescent girls of Cooch Behar district, West Bengal, India. Methods: A community based cross sectional study was conducted from April to October, 2023 among urban (n=232) Bengalee Hindu (15-18) years old adolescent school going girls of Urban municipal areas of Cooch Behar district, West Bengal, India. Data were collected after informing the purpose of the study school authorities, students and their parents and written consent was taken from school authorities before data collection. Anthropometric measurement height (cm), weight (kg) was recorded. BMI was calculated and the values of BMI were plotted on age specific WHO Charts for height and BMI. Age, diet, fast food consumption, having carbonated drink, duration of watching T.V., use of mobile, physical activity and transportation to school were included in the schedule. All statistical analysis was done using SPSS 20 and WHO Anthro Plus software. Results: In the present study, prevalence of overweight-obesity among Bengalee Hindu girls was 26.72%. Contributing factors, like, diet, fast food consumption, having carbonated drink, use of mobile and physical inactivity was significantly associated overweight-obesity. Conclusions: Obesity was a major problem among urban adolescents.